FEMALE ATHLETE TRIAD - PROBABLE BUT DIFFICULT TO CONFIRM IN FEMALE ICE HOCKEY PLAYERS - Patricia Katherine Doyle-Baker; Leanne P McLean; Tak Fung (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2018)
Female hockey players have high energy expenditure and may enter a negative energy balance (EB) without noticeable body composition changes. Menstrual cycle (MC) and luteal phase (LP) length, EB, and bone mineral density (BMD) were tracked over nine months (mean, SD, ±) in 12 ice hockey players (HP; age 21.1 ± 3.4 yrs; height (HT) 165.9 ± 4.6 cm; weight (WT) 64.7± 8.1 kg, body fat percent (BF%) 22.8 ± 3.8%) and 12 non-athlete controls (C; age 21.4 ± 2.8 yrs., HT 169.5 ± 5.5 cm; WT 65.4 ± 5.4 kg; BF% 20.0 ± 3.1%). HP MC (35.8 ± 11.2 days) was longer than C (29.8 ± 4.3 days) and HP LP (10.1 ± 2.1 days) was also longer than C (9.6 ± 2.8 days). Anovulation occurred in 50.0 % of HP versus 39.2 % of C. No group BMD differences were observed in lumbar spine (p = 0.9), hip (p = 0.5), and radial (p = 0.7) sites. A negative EB was identified (HP = -1026.52 ± 450.1; C = -780.00 ± 310.19 kcal / day), yet no significant within-group differences in WT (HP p = 0.7; C p = 0.8), BF % (HP p = 0.97; C p = 0.6), or fat free mass (HP p = 0.6; C p = 0.98) were found over the study duration. Rigorous hockey schedule likely contributed to 28 % completion of the Basal Body Temperature and MC recordings in HP compared to 70 % in C. Both groups entered a state of negative EB, but did not exhibit a BF % change associated with the Female Athlete Triad.